Identifying mixtures of metals by multi-isotope analysis: disentangling the relationships of the Early Bronze Age swords of the Apa-Hajdúsámson type and associated objects - Berger, Daniel; Brügmann, Gerhard; Bunnefeld, Jan-Heinrich; Pernicka, Ernst (Archaeometry, 2022)
This pilot study addresses the analytical characterisation of 26 well-known bronze objects of the Early and Middle Bronze Age of Central and Northern Europe. Besides swords and axes of the hoards from Apa, Téglás and Hajdúsámson, the investigation includes the famous Sky Disc and its accompanying finds from the Nebra hoard and several full-hilted swords from Period I in Denmark. In contrast to former publications, the isotopic systematics of lead, tin and copper are the focus of the present investigation. With a combined approach, we try to relate the typologically closely linked or otherwise related artefacts with chemical and isotopic proxies by identifying mixing scenarios. The results demonstrate that artefacts from different locations are most likely not directly linked, but mixing lines across isotope systems suggest a production of the items from common sources by mixing of bronze batches (e.g., bronze ingots), which were probably disseminated between 1600 and 1500 bce. This helps to correlate objects of different locations with each other and to draw conclusions upon typological and cultural connections. Isotopic and chemical correlations of objects within the individual hoards, on the other hand, allow reconstructions of metallurgical practices in single workshops, which, for example, implies recycling of metal scrap.
First published: 26 August 2021
Gesehen am 27.03.2023